Analysis of the Influence of Mental Workload on Employee Performance with the Subjective Workload Assessment Technique (SWAT) Method at PT. Bumi Jasa Utama (Kalla Group) - Pratiwi, Putri Ling Ananda; Pawennari, Andi; Afiah, Irma Nur (Omnia Tempus, 2022)
Purpose: This study aimed to measure the mental workload experienced by employees in the finance department and to analyze the effect of mental workload on employee performance. Design/methodology/approach: This study used the Subjective Workload Assessment Technique (SWAT) method to measure the mental workload faced by employees who must perform various activities in their work. Findings: The results of this study indicate that the time load factor (T) is the dominant factor affecting employee workload because employees are required in terms of time to perform each activity included in the work process quickly, precisely, and in large quantities every day. Mental workload has a direct and significant positive effect on employee performance. Research limitations/implications: Data collection was only conducted on employees of the Finance Department of PT Bumi Jasa Utama. Practical implications: Based on the results of this study, the company is expected to increase the number of employees in the finance department to streamline time and minimize the workload of each employee in the finance department. The company is also expected to improve service and service quality by considering employee comfort and performance. Originality/value: The condition of employees who are given a high workload and ongoing causes stress and anxiety, so it is necessary to measure mental workload and the effect of mental workload on employee performance.